1975
DOI: 10.1002/ps.2780060506
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of benfluralin in soil and its uptake by carrots

Abstract: Analytical methods are described for the determination of residues of benfluralin in soil and carrots. All plots treated with 1.3 or 1.9 kg benfluralin/ha produced average carrot yields significantly higher than untreated plots. Degradation of benfluralin in soil was very slow during the winter. As the temperature rose, the rate of benfluralin decline was accelerated; 324 days after incorporation, benfluralin residues were reduced to about 11 and 14% of the applied dose. The average total residues of benflural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…8 with the degradation rate constant sir (1 /sec) of pesticides in edible root, volume of edible root Vr (cm3) and concentration of chemicals in the root Cr (g/cm3). M = Ar X Vr X Cr (8) On the basis of the above considerations, the intake of pesticide IA (g) in the period t (sec) can be expressed by combining equations (2), (4), (7) and (8) as below.…”
Section: Loss By Metabolism/degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…8 with the degradation rate constant sir (1 /sec) of pesticides in edible root, volume of edible root Vr (cm3) and concentration of chemicals in the root Cr (g/cm3). M = Ar X Vr X Cr (8) On the basis of the above considerations, the intake of pesticide IA (g) in the period t (sec) can be expressed by combining equations (2), (4), (7) and (8) as below.…”
Section: Loss By Metabolism/degradationmentioning
confidence: 99%
“…To date, the distribution of soil-treatment pesticides in edible roots has been studied using radiolabeled materials. [1][2][3][4][5][6][7][8][9] Studies have shown that more than 75% of the total amount of residue persisted in root peel when edible roots were exposed to lipophilic pesticides even though the peel accounts for only 10% of total weight.…”
Section: Introductionmentioning
confidence: 99%
“…Businelli and co-workers (53) studied the persistence of benfluralin in soil and its uptake by carrots.…”
Section: Herbicidesmentioning
confidence: 99%